2016
DOI: 10.1111/evo.13013
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in local adaptation of a specialist insect herbivore to its long-lived host plant

Abstract: Local adaptation of interacting species to one another indicates geographically variable reciprocal selection. This process of adaptation is central in the organization and maintenance of genetic variation across populations. Given that the strength of selection and responses to it often vary in time and space, the strength of local adaptation should in theory vary between generations and among populations. However, such spatiotemporal variation has rarely been explicitly demonstrated in nature and local adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…There is strong evidence that gene flow counteracts adaptation in spatially structured populations. Many studies observe a negative correlation between the degree of local adaptation and the spatial isolation of populations or their inferred immigration rates, consistent with the idea that diversifying selection is more effective in populations that are at least partially shielded from immigration (May et al 1975;Stearns and Sage 1980;King and Lawson 1995;Storfer and Sih 1998;Hendry and Taylor 2004;Nosil and Crespi 2004;Tack and Roslin 2010;Kalske et al 2016). Similar analyses of adaptation along spatial environmental gradients are less frequent, but two studies of insects observed that clinal variation in quantitative traits along elevational gradients was more pronounced under conditions expected to reduce gene flow (longer gradient: Bridle et al 2009; species with wingless adults: Levy and Nufio 2015).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…There is strong evidence that gene flow counteracts adaptation in spatially structured populations. Many studies observe a negative correlation between the degree of local adaptation and the spatial isolation of populations or their inferred immigration rates, consistent with the idea that diversifying selection is more effective in populations that are at least partially shielded from immigration (May et al 1975;Stearns and Sage 1980;King and Lawson 1995;Storfer and Sih 1998;Hendry and Taylor 2004;Nosil and Crespi 2004;Tack and Roslin 2010;Kalske et al 2016). Similar analyses of adaptation along spatial environmental gradients are less frequent, but two studies of insects observed that clinal variation in quantitative traits along elevational gradients was more pronounced under conditions expected to reduce gene flow (longer gradient: Bridle et al 2009; species with wingless adults: Levy and Nufio 2015).…”
Section: Introductionmentioning
confidence: 58%
“…Blue symbols and lines are the cool treatment (147C), and red is the warm treatment (217 or 227C). Error bars (51 SE), which are sometimes obscured by the symbols, were calculated over sample sizes of ∼400 individuals (A) or eight sibships (B) for latitude and of 10 sibships for elevation.E76 The American Naturalist and Taylor 2004;Bridle et al 2009;Tack and Roslin 2010;Kalske et al 2016)…”
mentioning
confidence: 99%
“…Emerging evidence also suggests that local adaptation in plant–herbivore interactions can vary across generations (Kalske et al . ), implying that studies of these interactions should be replicated across growing seasons or generations to evaluate dynamic patterns of local adaptation. Furthermore, local adaptation need not be reciprocal when there are antagonistic interactions between species.…”
Section: Question 2: How Do Agents Of Selection Interact To Generate mentioning
confidence: 99%
“…For example, by placing dark vs. light coloured plasticine mouse models in inland and beach habitats, Vignieri, Larson & Hoekstra (2010) demonstrated that predation is a causal agent of local adaptation for cryptic coloration in Peromyscus polionotus. Emerging evidence also suggests that local adaptation in plant-herbivore interactions can vary across generations (Kalske et al 2016), implying that studies of these interactions should be replicated across growing seasons or generations to evaluate dynamic patterns of local adaptation. Furthermore, local adaptation need not be reciprocal when there are antagonistic interactions between species.…”
Section: B a C K G R O U N D : A B I O T I C A N D B I O T I C A G E mentioning
confidence: 99%
“…Kalske et al . () found that the strength of local adaptation increases with increasing distance for populations of the herbivore Abrostola asclepiadis (Noctuidae) and their host plants. Similarly, our results also show that a generalist herbivore may be adapted to its local host populations.…”
Section: Discussionmentioning
confidence: 99%